(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
The present study verified how competition contingencies, when the participant is at an advantage or disadvantage compared to a virtual opponent, influence the accuracy of children´s self-report on their performances in a computerized game. Six children with typical development were exposed to the experimental conditions: Baseline, that evaluated participants’ self-report accuracy on their performances on the game, in the absence of planned competition contingencies; Competition-Advantage, that evaluated the influence of competition contingencies in which the participant is at an advantage compared to his oponent; and Competition-Disadvantage, presented in order to verify the influence of competition contingencies when the participant is at a disadvantage compared to his oponent. Results showed the influence of competition contingencies on self-report correspondence of three of six participants, what indicates the competition contingence as a control variable of verbal/nonverbal correspondence.